Դարձվածքները Կարնո բարբառի մի քանի խոսվածքներում - Մարկոսյան, Նարինե (ՀՀ ԳԱԱ ԼԻ հրատ.)
The purpose of this article is to speak about the study of idioms, unique linguistic means that are characteristic of several speeches of the Karin dialect and ensure the popularity of the given region. For this purpose, we have selected three different regions within the Samtskhe-Javakheti region of Georgia, i.e Damala in the Aspindza region (it is the only Armenian village out of 21 settlements within the Aspindza region), Vachiyan in the Akhalkalaki region, and Oral in the Akhaltsikhe region. As a result of the study it becomes clear that the Georgian-Armenian regions are notable for their abundant use of idioms, which we have tried to highlight in the present article. We have presented the idioms composed of the names of body parts according to the degree of closeness of components, then we have highlighted the winged words, blessings, curses, reprimands, flattering expressions, proverbs and sayings typical of only the given regions. It was noticeable that the eldest generation in the villages is more inclined to use these expressions, the elder generation also uses them in comparison with the younger generation, and the middle generation uses them less than the elder generation, but more often than the younger generation. В данной статье мы обращаемся к исследованию уникальных, непревзойденных языковых средств - фразеологизмам, характерным для нескольких диалектов Каринского диалекта и обеспечивающим популярность данного региона. Для этого были выбраны три населенных пункта Самцхе-Джавахкского региона Грузии: село Дамала области Аспиндза (единственное армянское село из 21 населенного пункта этой области), село Вачиан Ахалкалакского района и село Орал Ахалцихского района. В статье мы постарались осветить исследование, из которого становится ясно, что армянские районы Грузии отличаются богатым употреблением словосочетаний. Мы представили фразеологизмы со словами, называющими части тела, по степени близости компонентов, а затем выделили только крылатые слова, благословения, проклятия, укоризненные, ласкательные выражения, пословицы и поговорки, характерные для данного региона. Было заметно, что самое старшее поколение сел более склонно к использованию этих выражений, старшее поколение также употребляет их в отличие от младшего, среднее поколение – реже по сравнению со старшими и чаще по сравнению с младшими.
Keywords: Բարբառագիտություն